(untitled) (Fiep Bulletin - online, 2014)
This paper is the result of an ethnographic research performed in the institutional extension project "Children of Canudos", which started six years ago carried out by Centro Universitário Feevale/RS - Brazil, through the Physical Education Course and Body, Movement and Health research group. Capoeira was chosen for the study because it’s the activity which keeps children and teenagers since its beginning in 2000. The objective was to describe and analyze the meaning of the trajectory of capoeira in the six years of existence of Project "Children of Canudos" according to the children, parents and head teachers’ perception. Three school principals, seven children and seven guardians participated. The instruments collected were interviews, observations, field diary and documents. The results were: children considered the educator who works in the project as being a good, friendly, cheerful, playful, happy, cool teacher and someone special. They like the way he teaches, he’s a guide in sport. They confirmed that capoeira, to them, means health, physical activity, leisure, game, as well as sport and culture. They learned new things, like the ginga, meia-lua, the circle, in which everybody sing, dance and fight. In the parents’ view, their children improved their behavior at home (talking to them), at school, improved their grades and school performance, besides improving in relation to shyness, they made friends, learned how to respect people. As for the principals, they stated that the children learned respect, limits, rules, healthy competition (cooperation), the ludic.